A exclusão do cônjuge do rol de herdeiros necessários no projeto de reforma do código civil: consequências jurídicas e sociais sob a perspectiva de gênero - Pires, Edivânia de Castro (2025)
This Final Course Work aims to analyze the legal and social consequences of excluding the spouse from the list of necessary heirs, according to the proposal of Bill 04/2025 to reform the Civil Code of 2002. The main objective of this study was to analyze the legal and social implications of the proposal regarding the inheritance rights of the spouse, considering the diversity of contemporary family arrangements and the challenges of overcoming gender inequalities. A qualitative approach was followed, with documentary analysis and based on the final report of the Inheritance Law Subcommittee of the Commission of Jurists, on legislative and doctrinal texts and statistical data. This study researches the historical transformations of the succession of the spouse in Brazilian legislation, analyzes the assumptions of the reform project and reflects on the possible social implications resulting from its implementation. It was found that, although the reform seeks to increase the autonomy of the testator and adapt the law to current family configurations, the exclusion of the inheritance protection of the spouse can increase social inequalities, especially for women in vulnerable situations.